Пошаговое объяснение:
а) -25x=100;
Х=100:(-25)
Х=-4
б)1/3 х=-9
Х=-9:1/3
Х=-9*3
Х=-27
в) 24-х=10+6х
-х-4х=10-24
-5х=-14
Х=-14:(-5)
Х=2,8
г) 64х=4х+120
64х-4х=120
60х=120
Х=120:60
Х=2
д) х-1= 4/5
Х=4/5+1
Х=1 4/5
е) -2· (х-3)=0
-2х+6=0
-2х=-6
Х=-6:(-2)
Х=3
Пошаговое объяснение:
а) -25x=100;
Х=100:(-25)
Х=-4
б)1/3 х=-9
Х=-9:1/3
Х=-9*3
Х=-27
в) 24-х=10+6х
-х-4х=10-24
-5х=-14
Х=-14:(-5)
Х=2,8
г) 64х=4х+120
64х-4х=120
60х=120
Х=120:60
Х=2
д) х-1= 4/5
Х=4/5+1
Х=1 4/5
е) -2· (х-3)=0
-2х+6=0
-2х=-6
Х=-6:(-2)
Х=3